Helmut Lachenmann: Das Mädchen mit den Schwefelhölzern - Lachenmann, Helmut 1935-; Cambreling, Sylvain; SWR Vokalenensemble Stuttgart; SWR Sinfonieorchester (München ECM Records, 2004)
Helmut Lachenmann's advanced theories on sound production and the existential aspects of performance are put to the test in Das Mädchen mit den Schwefelhölzern (The Little Match Girl), his avant-garde opera based on texts by Hans Christian Andersen and Leonardo da Vinci. In performance, this work has a powerful impact, and much of that is attributable to the spectacle provided by the players. Lachenmann's complex gestures and scintillating effects are extraordinary by themselves, but the physical production of these sounds in live performance is critical to their reception because they define space and create situations that are central to the drama. On CD, all of this visual activity is lost, and the listener is left with approximately half of the experience. The recording leaves only an impression of sounds darting around the performance area, and their precise locations are impossible to sort out. One may imagine that something intense and provocative is happening, but after a few minutes, this exercise becomes tiresome. Eventually, the vocalizations of sopranos Eiko Morikawa and Nicole Tibbels and the instrumental effects of the SWR Sinfonieorchester blur into mere washes of sound, and the work begins to resemble musique concrète, rather than a theatrical piece. Recorded in 2002, this ECM double-disc has vivid sound.